In the Shadow of the Ivory Tower: How Universities are Plundering our Cities: by Davarian L. Baldwin - Bannier, Betsy J (Radical Teacher, 2021)
In today’s politically charged, anti-education climate, In the Shadow of the Ivory Tower should be required reading for every urban community organizer and higher education stakeholder. Davarian L. Baldwin blends captivating interview excerpts and thoroughly researched data to tell the stories of the winners and losers in and around well-known universities in urban areas from coast to coast. Cultural differences, policing problems, economic disparities, real estate transactions, taxes, and subsidies are all addressed. In the Shadow of the Ivory Tower is a powerful conversation starter about who really benefits from the physical presence of American universities, and how universities might change their tactics to expand those benefits to communities at large.